Futebol e turismo: possibilidades de aproximação entre o novo Mineirão e a Pampulha - Erick Alan Moreira Ferreira (2015)
This dissertation aimed to investigate the practice of football tourism in Belo Horizonte-MG, from the possibilities of approximation between the new Mineirão and Pampulha, before the coming of the new spatial logic of Brazilian football. Investigated specifically the treatment that the Pampulha receives by the municipal government regarding the appearance of leisure and tourism, the socio-economic profile of the visiting fans who attend the stadium in regular season games of Brazilian football (club competitions to the level regional, national and continental), the reasons that motivate them to travel to watch a football match, the tourist attraction exerted by the new Mineirão and tourism consumption performed in the region. This research is classified as qualitative and quantitative, exploratory and descriptive. As part of the qualitative/exploratory stage, took place bibliographical and documentary research, as quantitative/descriptive part, was done by conducting a field survey. The instrument used for data collection was the form. The forms were applied to fans on game days held in the Mineirão, in internal and external areas of the stadium. In order to participate in the survey, the fan should be over eighteen years of age and has no fixed dwelling in the city of Belo Horizonte. At the end of the study, participated 335 fans. With the completion of exploratory research, it was identified that the Pampulha, even though it was created in the 1940s with the aim of becoming the reference area of the state capital in terms of social experiences, especially in relation to tourism, this activity began develop, in fact, only in the 2000s, when it became allowed non-residential use of the area, allowing the installation of economic activities, for example, tourist services. With interventions carried out for the World Cup 2014, the Pampulha established itself as a tourist space, since there was expansion and improvement of its attractions, equipment, infrastructure and services for the tourism industry. On the data collected in the field research, we identified that the visitor supporter socioeconomic profile presents particular characteristics consistent with this kind of audience, which is defined as predominantly married, adult and high level with regard to schooling and income, and Moreover, in line with the commodification scenario of Brazilian football, much longer it became socio-fans and the minority part of cheerleading. Most visiting fans traveling with the main objective to watch a football match at the stadium and the intrinsic values to the new Mineirão, are factors that motivate them to want to attend it. Visitors fans are mostly tourists and staying primarily in hotel/hostel, and when the main purpose of trip is football, Pampulha is the most demanded area. With regard to tourism consumption in Pampulha, the minority of visiting fans held other activities besides football experience, however, one realizes that the ride on the edge of Lagoa da Pampulha, consumption in bars and restaurants and the visit the Church of St. Francis of Assis and the zoo, are the most frequent activity among fans that add the experience in football with tourism. Therefore, both the interventions occurred in the urban landscape of Pampulha that formed as a tourist space as the tourist flow from the footballing demand, it is believed that football might be thinking beyond the sporting dimension, as a tourist attraction capable of promoting tourism in the locality.